Ultrasonography: a diagnostic choice to localise intra uterine contraceptive devices - Sethi, Prabh D.; Goyal, Nisha; Garg, Anil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine devices are important method of contraception. They are more effective than oral contraceptives. They are also reversible forms of contraception. They provide contraception for years. Sonography is very useful in localization of intra uterine contraceptive devices. Before insertion, it tells us about uterine anomalies, tumours and shape of uterus. After IUCD insertion, it is helpful for locating IUCD and confirming the place where required and also tells us its relative position at follow up also. Methods: In this study, sonography is used for localization of Cu-T, IUCD by its four very important features namely, type-specific morphology, posterior acoustic shadowing, entrance-exit reflection, anechoic halo around the IUCD. Results: In this study, it was observed that 100 % localization of IUCD is possible by these parameters. Conclusions: It was concluded that ultrasonography acts as diagnostic tool for localization of Copper T IUCD.